THYROGLOSSAL DUCT CYST, PEDIATRIC PATHOLOGY WITH MULTIDISCIPLINARY MANAGEMENT - Elena Ţarcă; Mioara-Florentina Trandafirescu; Doina Mihăilă; Elena Cojocaru; B. Savu; S. G. Aprodu (Romanian Society of Oral Rehabilitation, 2016)
Aim of the study The thyroglossal duct cyst is a congenital malformation caused by the persistence of the thyreoglossal duct, which connects the root of the tongue with the thyroid. It is the most common cervical cyst, as it occurs in about 7% of the population and constitutes 70% of the congenital malformations that affect the cervical area. Starting with 1920, the gold standard of the treatment of this condition is cyst excision using the described by Sistrunk. Clinical examination is usually enough to set a diagnosis of thyroglossal duct cyst, but confirmation by ultrasound scanning is useful and even necessary to reveal normally or ectopically located thyroid tissue. The primary aim of this study is to describe and present the author's experience with an aparent simple but sometime challenging and multidisciplinary children condition, thyroglossal duct cyst. Material and Methods We conducted a retrospective analytical study on 26 children with thyroglossal duct cyst hospitalized in the Pediatric Surgery Department of the -Saint Mary‖ Emergency Children's Hospital of Iaşi for a period of 3 years. Results The mean age at the time of examination was 6.4 years, but 53.8% of the children were younger than 6 years. The diagnosis was clinical, confirmed by ultrasound scanning of the soft cervical parts in only 69.2% of the cases. A thyroid ultrasound scanning was performed in only 53.8% of the patients. The thyroglossal duct cyst was surgically removed by the Sistrunk techniques in 84.6% of the patients. Ectopic thyroid tissue was detected in the cyst walls in two of the patients, whereas in another patient the histopathology examination detected cyst invasion inside the hyoid bone (the fifth case reported in literature). The cyst reoccurred in a single patient and it required another surgical procedure. Literature reports a rate of about 1% of malignant thyroglossal duct cysts, usually papillary thyroid carcinoma, and therefore preoperative imaging and histopathology examinations should always be included in the therapeutic protocol. Conclusions Clinical examination may be enough to set a diagnosis of thyroglossal duct cyst, but confirmation by ultrasound scanning and laboratory tests is useful and even necessary.